(untitled) (American Journal of Islam and Society, 1999)
This paper revisits the debate on the rhythmic recitation of the Quran. It examines the arguments made by those who favor rhythmic recitation and those who oppose it by scrutinizing their Quranic and traditional sources. The paper examines all the ahadith and the Quranic ayahs that relate to the subject and concludes that as long as the rules of tajwid are followed it is permissible to embellish the recitation of the Quran with rhythm as well as modulated voice.